Inhibition of biofilm formation by D-tyrosine: Effect of bacterial type and D-tyrosine concentration - C. Yu; X. Li; Zhang, N.; Wen, D; C. Liu; Li, Q. (Water research, 2016)
D-Tyrosine inhibits formation and triggers disassembly of bacterial biofilm and has been proposed for biofouling control applications. This study probes the impact of D-tyrosine in different biofilm formation stages in both G+ and G- bacteria, and reveals a non-monotonic correlation between D-tyrosine concentration and biofilm inhibition effect. In the attachment stage, cell adhesion was studied in a flow chamber, where D-tyrosine caused significant reduction in cell attachment. Biofilms formed by Pseudomonas aeruginosa and Bacillus subtilis were characterized by confocal laser scanning microscopy as well as quantitative analysis of cellular biomass and extracellular polymeric substances. D-Tyrosine exhibited strong inhibitive effects on both biofilms with  an effective concentration as low as 5 nM; the biofilms responded to D-tyrosine concentration change in a non-monotonic, bi-modal pattern. In addition, D-tyrosine showed notable and different impact on EPS production by G+ and G- bacteria. Extracellular protein was decreased in P. aeruginosa biofilms, but increased in those of B. subtilis. Exopolysaccharides production by P. aeruginosa was increased at low concentrations and reduced at high concentrations while no impact was found in B. subtilis. These results suggest that distinct mechanisms are at play at different D-tyrosine concentrations and they may be species specific. Dosage of D-tyrosine must be carefully controlled for biofouling control applications.